ANALISIS PROGRAM PEMBERDAYAAN EKONOMI PETANI DALAM MENANGGULANGI KEMISKINAN DI DESA LESENG KECAMATAN MOYO HULU - Yayat Fitriani; U Usman; Abdul Rahim; N Nurmalasari (Jurnal Ekonomi & Bisnis, 2020)
This study aims to know the economic empowerment program of farmers in overcoming poverty in Leseng Village, Moyo Hulu Sub-District. Type of this study was descriptive study. The type of data used in this study was qualitative data obtained directly from the source through interviews. Informants in the study were divided into two, namely key informants who were policy makers and supervisors consisting of village heads and Village Owned enterprise (BUMDes) officers, and key informants consisting of farmers who were targeted by the policy. Data analysis was done using data analysis techniques of Miles and Huberman which consisted of data collection, data reduction, data presentation and drawing conclusions. The validity of the data was tested using triangulation. Based on the results of study showed that in the implementation of economic empowerment for farmers in Leseng Village, which has done through several development efforts including counseling programs, such as the construction of irrigation channels, capital loans, seeds and medicines, could make it easier for people who have difficulty obtaining loans and difficulties from reaching water although the eater supply was still limited, it can help community.